Integrating perspectives from engineering ethics into the study of technology: A synthesis of research on critical cases - Konstantis, Konstantinos; Tsakalakis, Thomas (Bioethica, 2024)
Ethics play a crucial role in the work of engineers, and therefore in everyone’s life, from the field of artificial intelligence ethics to the fields of environmental ethics and biomedical ethics. Analyzing critical technology case studies from the perspective of engineering ethics affords us the opportunity to understand if engineers acted ethically or not in a given situation, what they could have done otherwise, and what they should bear in mind for future case studies regarding ethics. In this article, at first, we draw upon primary and secondary sources in order to analyze two case studies that are of critical importance because, according to the engineers involved in them, it was likely they could have led to fatal accidents. Then, we offer engineering ethics perspectives into the studies. Studying engineering cases from an engineering ethics perspective is crucial for two reasons. First, engineers could have a more completed point of view regarding engineering ethics in order to understand how to act ethically during their work. Second, engineers and others (philosophers of technology, historians of technology, etc.), who analyze these cases in retrospect, could present a more adequate story that would be more useful for the engineers who are taught from it.